2021
DOI: 10.3897/arphapreprints.e73387
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Nicotiana rupicola sp. nov and Nicotiana knightiana (Paniculatae, Solanaceae), a new endemic and a new record for the flora of Chile

Abstract: Nicotiana knightiana is recorded for the first time for the flora of Chile. A new species of Nicotiana, endemic to the coast of the Coquimbo region is described and illustrated. Molecular analysis placed the new species within the section Paniculatae, as sister to Nicotiana cordifolia, endemic to Juan Fernandez islands. The new species can be considered critically endangered (CR) according to the IUCN categories for its restricted and fragmented distribution, small population number, and the threat that urbani… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…Specific status based on recent studies and reports published after April 2019 (not included in Palchetti et al, 2020 ) has been considered. This included studies, such as the revision of the genus Schizanthus ( Morales-Fierro et al, 2020 ; Lavandero et al, 2021 ); updates in Nolana ( Hepp and Dillon, 2018 ); the Morelloid clade of Solanum in Argentina ( Knapp et al, 2020 ); cryptic species recently reported ( Moreira-Muñoz and Muñoz-Schick, 2020 ); and new Petunia and Nicotiana species ( Greppi et al, 2019 ; Santilli et al, 2021 ). After a first cleaning, data from ex situ living collections that introduced species, hybrid taxa, and records with doubtful or incomplete identification at the species level were excluded.…”
Section: Methodsmentioning
confidence: 99%
“…Specific status based on recent studies and reports published after April 2019 (not included in Palchetti et al, 2020 ) has been considered. This included studies, such as the revision of the genus Schizanthus ( Morales-Fierro et al, 2020 ; Lavandero et al, 2021 ); updates in Nolana ( Hepp and Dillon, 2018 ); the Morelloid clade of Solanum in Argentina ( Knapp et al, 2020 ); cryptic species recently reported ( Moreira-Muñoz and Muñoz-Schick, 2020 ); and new Petunia and Nicotiana species ( Greppi et al, 2019 ; Santilli et al, 2021 ). After a first cleaning, data from ex situ living collections that introduced species, hybrid taxa, and records with doubtful or incomplete identification at the species level were excluded.…”
Section: Methodsmentioning
confidence: 99%